2017
DOI: 10.1111/jre.12515
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of photodynamic therapy and alendronate on alveolar bone loss in rats with ligature‐induced periodontitis

Abstract: Combined approach therapy of PDT + ALN 0.25 mg/kg demonstrated a protective effect on alveolar bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Camacho‐Alfonso et al . evaluated their potential synergistic effect in a murine model (82). The combined approach therapy of PDT and alendronate (0.25 mg kg −1 ) demonstrated a significant protective effect on reducing bone loss.…”
Section: Osseointegration and Bone Repairmentioning
confidence: 99%
“…Camacho‐Alfonso et al . evaluated their potential synergistic effect in a murine model (82). The combined approach therapy of PDT and alendronate (0.25 mg kg −1 ) demonstrated a significant protective effect on reducing bone loss.…”
Section: Osseointegration and Bone Repairmentioning
confidence: 99%
“…As an explanation of the results of the present study, it should be highlighted that the dysfunctional damage at the endothelium level found in patients with periodontitis and with CVD can be determined by a specific inflammatory and immune pathway in which MPO modulates a response towards pathogenic bacteria of the oral biofilm which are exacerbated during the active phases of periodontal damage. It has also been shown that MPO, during periodontal disease, mediates the immune response at the endothelial level through specific heat shock proteins which has been shown to be useful for stimulating the production of cross-reactive T cells [47][48][49][50][51][52]. In this regard, this process which sees MPO as a key modulator [53][54][55][56][57][58], has also been shown to influence the host defense mechanism that determines a subsequent activation of endothelial cell production [55,[58][59][60][61][62][63] which leads to an increased risk of future tissue damage effects due to periodontal pathogens bacteria in several oral diseases [43,[64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to evaluate combination of topical use of ALN and aPDT. Camacho‐Alonso et al 48 also evaluated the synergistic effect of aPDT and ALN on alveolar bone loss in rats with ligature‐induced periodontitis, but with systemic use of alendronate. They also evaluated whether different ALN dosages had different results and concluded that a combined approach of aPDT plus ALN 0.25 mg/kg demonstrated a protective effect on alveolar bone loss.…”
Section: Discussionmentioning
confidence: 99%